Research and practice of SRv6 for integrated carrying of video cloud - Chongfeng XIE; Wenjie JIANG; Chenhao MA; Hao YAN; Sifei WANG; Cong LI; Yunqing CHEN (Dianxin kexue)
SRv6 is newly emerging,source routing-based technology,which aims to realize network programmability by steering a packet through an ordered list of instructions in the IPv6 extension header,so as to meet multiple requirements,such as fast service provisioning.Based on the field trial of SRv6 in the production network in Sichuan province,the SRv6 solution for integration the video clouds in multi-domain networks was illustrated,which had shown the advantages of SRv6 in service agility,secure separation,bandwidth elasticity and inter-domain deployment.In addition,the challenges of SRv6 were listed and development policy was given in the end.